IMPLEMENTASI MODEL PEMBELAJARAN INDOOR-OUTDOOR PADA MATA PELAJARAN FIQIH DI MI MA’ARIF AT TAQWA KALANGANYAR - Ahmad Hanif Fahruddin; Ma'rifatul Islamiyah (Akademika, 2018)
Thesis entitled "Implementation of Indoor-Outdoor Learning Model at MI Ma'arif At-Taqwa Kalanganyar Lesson Year 2017/2018" This is the result of qualitative research that aims to answer the question of how the process of learning model, supporting and penghamabat factors and how to overcome the inhibiting factor in this indoor-outdoor learning.With the rapid development of the era, the world of education is required to find innovation and creativity in the learning process, especially in the lessons of Islamic Education and especially the subjects of Fiqh, this is to improve the results and quality of education in preparing the next generation of high-quality nation. One of them is the use of a variety of learning models both outside and inside the classroom. As in the case of MI Ma'arif At-Taqwa Kalanganyar Karanggeneng Lamongan. The research approach used is qualitative descriptive with the type of case study research on the object. Data collecting was done by interview of informant, in this research that is interview to teacher of fiqih subject and some student become research object.The results obtained are First, the implentation of indoor-outdoor learning model is done alternately in every week. Second, the supporting factors of the learning process are the creative teachers, the enthusiasm of the students, the means, the tools, the available media, and the environment. While the inhibiting factors of learning are too tense, the cost is not small, the teacher is difficult to manage the many students, the teacher is more intensive in guiding, preparation and learning process also takes a very long time. Third, to overcome the existing inhibiting factors teachers must have high innovation in overcoming the obstacles that arise in the learning process.